Association of HLA-B27 antigen with clinical and laboratory parameters in patients with juvenile idiopathic arthritis - Adisa Čengić; Velma Selmanović; Sniježana Hasanbegović; Nedim Begić; Emina Karčić; Elma Fejzić (Medicinski glasnik, 2022)
Aim: To analyse the association of human leukocyte antigen B27 with clinical and laboratory parameters in patients with juvenile idiopathic arthritis (JIA) at the disease onset. Methods: A retrospective review of medical records of 25 HLAB27 positive and 25 HLA-B27 negative JIA patients was performed. The diagnosis of JIA was based on the 1997-2001 International League Against Rheumatism (ILAR) criteria. Collected data: age, sex, HLA- B27 antigen presence, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid-factor (RF), antinuclear antibody (ANA), fever, rash, uveitis, enthesitis, inflamed joints and subtype of JIA. Results: HLA- B27 positive study group had more boys (p=0.01), higher erythrocyte sedimentation rate (p=0.038), higher presence of fever (p= 0.025) and enthesitis (p=0.024). Any significant difference in age of the disease onset, CRP, ANA, RF, rash, uveitis, inflamed joint and dactylitis was not noticed. The most common subtype of JIA in the HLA-B27 positive patients was ERA (60%). Conclusion: This study showed that the presence of HLA- B27 antigen plays a significant role in determining the presenting clinical and laboratory characteristics in JIA patients.
Keywords: arthritis; children; human leukocyte antigen